Biomonitoring of polycyclic aromatic hydrocarbons in the urine of lactating mothers: Urinary levels, association with lifestyle factors, and risk assessment. (1st January 2021) - F. Fernández, Sandra; Pardo, Olga; Pastor, Agustín; Yusà, Vicent; ,; Vento, M.; Cernada, M.; Gormaz, M.; Kuligowski, J.; Sánchez, A.; Torres, E.; Correcher, P.; et al.
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are pollutants produced during incomplete combustion of organic matter and several industrial processes. Humans can be exposed to PAHs through ingestion of food, inhalation of tobacco smoke or polluted air, and dermal contact, causing immunologic, developmental, and reproductive problems. In the present research, eleven metabolites of PAHs were analyzed in the urine of 110 lactating women living in Spain (2015). PAH metabolites were extracted from the urine samples by liquid-liquid extraction and their determination was performed by liquid chromatography coupled to tandem mass spectrometry. In addition, information on lifestyle and dietary habits of the participants was collected using a questionnaire. All the PAH metabolites were detected in more than 70% of the samples, except for 3-hydroxybenzo(a)pyrene which was detected in less than 1% of the samples. The highest urinary levels were found for naphthalene metabolites, with geometric means of 0.8 (1-hydroxynaphthalene) and 7.1 ng ml −1 (2-hydroxynaphthalene). The statistical analysis showed that smoking status, as well as the ingestion of certain food groups (vegetables, cereals, oils and fats, smoked fish and coffee), were the main influencing factors of exposure to PAHs. The estimated daily intake (EDI) was calculated for naphthalene, fluorene, phenanthrene, and pyrene, ranging from 6 to 1522 ng kg −1 ·day −1 . The non-cancer risk associated to PAH exposure was estimated, showing hazard quotients (HQs) and hazard indexes (HIs) below 1. Therefore, it did not reveal a significant health risk for Spanish women due to PAH exposure. Graphical abstract: Image 1 Highlights: More than six PAH urinary metabolites were detected in 100% of the women. Smoker women had higher levels of OHPAHs in their urines. Dietary habits of the participants were associated to the exposure to PAHs. Estimated daily intakes ranged from 6 (fluorene) to 1522 ng/kg-day (naphthalene). Non-cancer risk assessment resulted in Hazard Quotients and Hazard Indexes <1. Abstract : Eleven urinary PAH biomarkers were analyzed in Spanish women through biomonitoring, concluding that there is no potential health risk due to PAH exposure.